1989
DOI: 10.1182/blood.v73.6.1525.bloodjournal7361525
|View full text |Cite
|
Sign up to set email alerts
|

The activation of the contact phase of coagulation by physiologic surfaces in plasma: the effect of large negatively charged liposomal vesicles

Abstract: The endogenous, negatively charged surface that induces activation of the contact coagulation factors was investigated in plasmas taken from women in late pregnancy and control subjects of child-bearing age. The plasmas from the two groups of subjects were incubated at 4 degrees C for 24 hours either in plastic or in glass tubes and the factor VII coagulant activity (VIIc) was assayed in the treated plasmas. The activation of factor VII under these conditions involves the generation of enzymes derived from fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…2), which is a component of the contact system of blood coagulation which also includes prekallikrein, HMW kininogen and factor XI. Because the main physiological activators of factor XII include fatty acids and the surface of certain types of lipoprotein particles (Mitropoulos et al 1989), analysis of factor XIIa during differential PUFA administration was of special interest. In contrast to the effect on extrinsic factor VIIa, surgical trauma was of minor influence for intrinsic factor XIIa levels.…”
Section: Discussionmentioning
confidence: 99%
“…2), which is a component of the contact system of blood coagulation which also includes prekallikrein, HMW kininogen and factor XI. Because the main physiological activators of factor XII include fatty acids and the surface of certain types of lipoprotein particles (Mitropoulos et al 1989), analysis of factor XIIa during differential PUFA administration was of special interest. In contrast to the effect on extrinsic factor VIIa, surgical trauma was of minor influence for intrinsic factor XIIa levels.…”
Section: Discussionmentioning
confidence: 99%
“…How dietary fat promotes activation of FVII is unclear. It has earlier been proposed that triglyceride-rich lipoproteins [chylomicrons and very low density lipoproteins (VLDL)] are capable of activating FXII to FXIIa, and that FXIIa subsequently may cleave FVII zymogen to the active form, FVIIa (8,15,16). Recent observations by Mitropoulos et al indicate that it is rather products from the lipolytic degradation of triglyceride-rich lipoproteins than the lipoproteins themselves that promote the initial activation of FXII (17).…”
Section: Discussionmentioning
confidence: 99%
“…Blood samples were drawn at 8.00 h. 16.30 h and 19.30 h after 10 min of standardized resting (5 min in a chair followed by 5 min of supine resting). Blood samples at 8.00 h were drawn after at least 10 h fasting and non-smoking, and 24 h abstention from alcohol.…”
Section: Blood Samplingmentioning
confidence: 99%
“…Several in vitro experi ments showed that when stearic acid or vesicles, with a negative charge and size similar to TRLP, were added to plasma, FVIIc increased in a dose-dependent manner. Oleic acid and other unsaturated fatty acids had no effect on FVIIc (39,40). Lipoprotein lipase (LPL) seems to be A 2% lower important in this reaction; when plasma of hypertriglyceridaemic patients with LPL deficiency was treated with LPL factor XII was promptly activated (41).…”
Section: Activation Of Factor VII By Negatively Charged Surfacesmentioning
confidence: 99%